The Influence of Kelana Coffee Consumer Perceptions and Preferences on Consumer Purchasing Interest in Surabaya - Nur Anisah; Sonja Andarini (Universitas Muhammadiyah Jakarta, 2026)
The focus of this research was on the emerging trend of mobile coffee services in Surabaya, specifically examining Kopi Kelana, the first electric-bike-based coffee pioneer in the city. To address the research inquiries, this study adopted a quantitative associative approach focusing on the relationship between Purchase Intention (Y) as the dependent factor and two independent elements: Consumer Perception (X1) and Consumer Preference (X2). Data collection involved a five-point Likert scale instrument, spanning from strongly disagree to strongly agree, to quantify each research indicator. The target population included individuals in Surabaya familiar with the Kopi Kelana brand. Furthermore, a purposive sampling strategy was implemented under a non-probability framework, specifically targeting Surabaya residents who had previously interacted with mobile coffee service models. A total of 157 respondents participated and provided valid data for analysis. Data analysis was conducted using instrument tests (validity and reliability), classical assumption tests, and multiple linear regression analysis. The findings of this study showed that consumer perception and preference had a favorable and on purchase intention, both simultaneously and partially (F = 149.759, p < 0.05). The regression analysis indicated that positive perceptions regarding quality and brand identity, coupled with strong preferences for taste variety, significantly enhanced consumer interest. It was concluded that maintaining a unique brand identity and high service standards were crucial for the sustainability of mobile coffee businesses in an urban environment.